A genealogy of metatheory in IR: how 'ontology' emerged from the inter-paradigm debate. Issue 1 (29th December 2016) - Hamilton, Scott
Abstract : Drawn from the philosophy of science, metatheory is generally defined in International Relations (IR) as 'theorizing about theory' by examining a theory's ontology or epistemology. Yet, despite being available to IR since at least the 1940s, metatheory 'exploded' into IR only in the late-1980s. What explains this sudden proliferation of metatheory in IR's literature? This article answers this question by conducting a genealogy of metatheory in IR. It begins by offering a four-step heuristic guide for conducting a genealogical analysis. Then, bracketing IR's traditional historical narratives, it problematizes a tacit practice undergirding IR's present use of metatheory: theorizing about the 'world' using the philosophy of science. Tracing and interpreting the transformations of this practice through scholarship from the 1940s to the present reveals how metatheory emerged unexpectedly from what is now considered to be an outmoded and forgotten event: the inter-paradigm debate (IPD) of the mid-1980s. The IPD transformed what had always been conceptualized as a single, dynamic world for IR theory, into plural, static, theoretical worlds best (meta)theorized through a concept of ontology drawn from scientific realism. In sum, this genealogy demonstrates the implicit power that explicit theoretical practices wield over IR scholars, tacitly conditioning the discipline's conceptual possibilities and limits.